2017
DOI: 10.1186/s12974-017-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure is a risk factor for adult neuropathic pain via aberrant neuroimmune function

Abstract: BackgroundClinical studies show that prenatal alcohol exposure (PAE) results in effects that persist into adulthood. Experimental animal models of moderate PAE demonstrate that young adults with PAE display potentiated sensitivity to light touch, clinically termed allodynia, following sciatic nerve chronic constriction injury (CCI) that coincides with heightened spinal glial, spinal macrophage, and peripheral immune responses. However, basal touch sensitivity and corresponding glial and leukocyte activation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 97 publications
(110 reference statements)
11
34
0
Order By: Relevance
“…Additional evidence exists supporting the possibility that PAE augments astrocyte and microglial activation in the dorsal horn of the spinal cord in neuropathic adult male rats. That is augmented expression of Iba-1, a well-characterized microglial activation marker, and GFAP (Figure 1 B) were observed in PAE rats with CCI ( 52 , 53 ). In line with these observations, analysis of cytokine levels in sham-treated PAE rats revealed that DRG IL-10 protein levels are remarkably suppressed, with IL-10 suppression greatest in PAE neuropathic rats compared with control-treated rats ( 52 ).…”
Section: Spinal Glial-immune Responses That Are Altered By Moderate Pmentioning
confidence: 86%
See 3 more Smart Citations
“…Additional evidence exists supporting the possibility that PAE augments astrocyte and microglial activation in the dorsal horn of the spinal cord in neuropathic adult male rats. That is augmented expression of Iba-1, a well-characterized microglial activation marker, and GFAP (Figure 1 B) were observed in PAE rats with CCI ( 52 , 53 ). In line with these observations, analysis of cytokine levels in sham-treated PAE rats revealed that DRG IL-10 protein levels are remarkably suppressed, with IL-10 suppression greatest in PAE neuropathic rats compared with control-treated rats ( 52 ).…”
Section: Spinal Glial-immune Responses That Are Altered By Moderate Pmentioning
confidence: 86%
“…While speculative, glial cells may remain primed following an initial stimulation during gestational development (i.e., PAE), with classic activation markers returning to basal levels. However, these previously stimulated glia may develop an increased propensity for enhanced responses following subsequent immune stimulation ( 52 , 53 ). That is, it is possible under some circumstances that classic glial activation markers are uncoupled from their primed state such that basal levels of these markers are observed, yet these same glia over-respond to normal stimuli.…”
Section: Moderate Pae Shapes Neuroimmune Responses To Subsequent Inflmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, prenatal alcohol can increase susceptibility to substance abuse via indirect mechanisms. For instance, FASD are characterized by a higher vulnerability to stress, depression/anxiety disorders (Hellemans et al, 2010), and aberrant pain sensitivity (Sanchez et al, 2017).…”
Section: A Priming Role Of the Early Alcohol Experience?mentioning
confidence: 99%